Cytosolic caspases mediate mislocalised SOD2 depletion in an in vitro model of chronic prion infection - Layla Sinclair; Victoria Lewis; Steven J. Collins; Cathryn L. Haigh (The Company of Biologists, 2013)
SUMMARY Oxidative stress as a contributor to neuronal death during prion infection is supported by the fact that various oxidative damage markers accumulate in the brain during the course of this disease. The normal cellular substrate of the causative agent, the prion protein, is also linked with protective functions against oxidative stress. Our previous work has found that, in chronic prion infection, an apoptotic subpopulation of cells exhibit oxidative stress and the accumulation of oxidised lipid and protein aggregates with caspase recruitment. Given the likely failure of antioxidant defence mechanisms within apoptotic prion-infected cells, we aimed to investigate the role of the crucial antioxidant pathway components, superoxide dismutases (SOD) 1 and 2, in an in vitro model of chronic prion infection. Increased total SOD activity, attributable to SOD1, was found in the overall population coincident with a decrease in SOD2 protein levels. When apoptotic cells were separated from the total population, the induction of SOD activity in the infected apoptotic cells was lost, with activity reduced back to levels seen in mock-infected control cells. In addition, mitochondrial superoxide production was increased and mitochondrial numbers decreased in the infected apoptotic subpopulation. Furthermore, a pan-caspase probe colocalised with SOD2 outside of mitochondria within cytosolic aggregates in infected cells and inhibition of caspase activity was able to restore cellular levels of SOD2 in the whole unseparated infected population to those of mock-infected control cells. Our results suggest that prion propagation exacerbates an apoptotic pathway whereby mitochondrial dysfunction follows mislocalisation of SOD2 to cytosolic caspases, permitting its degradation. Eventually, cellular capacity to maintain oxidative homeostasis is overwhelmed, thus resulting in cell death.